Begin of the rainy season and dry spells in Southern Amazon using rain gauges - Argemiro Teixeira Leite-Filho; Verônica Yameê de Sousa Pontes; Marcos Heil Costa (PANGAEA, 2018)
Daily rainfall time series data from 112 rain gauges and a recent yearly 1-km land use dataset covering the period from 1974 to 2012 to evaluate the effects of the extent of deforestation at different spatial scales on the begin of the rainy season (Bi,j,t) and on the duration of dry spell (DSi,j,t) in southern Amazonia.
Supplement to: Leite-Filho, AT et al. (2019): Effects of deforestation on the onset of the rainy season and the duration of dry spells in southern Amazonia. Journal of Geophysical Research: Atmospheres, 124(10), 5268-5281, https://doi.org/10.1029/2018JD029537